The cascade equivalent A-H-circuit of the salient-pole generator on the base of the anisotropic model - Alexey Blanc (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In the scientific studies of the electric machines, cylindrical and Cartesian laminated models have long proved their operability when it is necessary to transform the general solutions of the partial differential equations into four-terminal network equations and to create the cascade equivalent circuits of the electric machines. In the case of the salient-pole machines, piecewise continuous Sturm-Liouville eigenfunctions are usually used as the general solution. Unfortunately, we cannot create the cascade equivalent circuit of the salient-pole electric machine when (to ensure both the uniqueness and the accuracy of the solution) the field is modeled with many piecewise continuous Sturm-Liouville eigenfunctions (in the zone of poles) and many sinusoidal functions (in the air gap). Nevertheless, the author developed the approximate method for modeling the magnetic field of the salient-pole electric machines when only one piecewise continuous Sturm-Liouville eigenfunction is used and many sinusoidal functions. In this case, it becomes possible to transform the general solution of the partial differential equation into four-terminal network equations and to create the cascade equivalent circuit of the salient-pole electric machine. In this paper, the cascade equivalent A-H-circuit of the synchronous salient-pole machine is considered (without using piecewise continuous Sturm-Liouville eigenfunctions but also without properties averaging).